A review on green integration into management control system - Abdul Aziz, Nor Azah; Foong, Soon Yau; Ong, Tze San; Attan, Hassan (Elsevier, 2015)
Environmental crises have major negative impacts on social, environment and economy in many countries. With the concerns on environmental issues, people and organizations need to adopt sustainability practices. A question arises on the role of accounting in enhancing the effectiveness of environmental practices. Therefore, this paper reviews on the role of management control system (MCS) in managing environmental or green issues and the extent of green integration into MCS. The literature review indicates that MCS plays a very important role in managing green issues. There are various interpretations, dimensions and levels of extent of green integration into MCS.